Mewujudkan Justice As Fairness: Analisis Ketidakmerataan Pelayanan Kesehatan di Indonesia Menurut Teori John Rawls - Maghfiroh, Laily (Media Hukum Indonesia (MHI), 2025)
This study aims to analyze the inequality of healthcare services in Indonesia based on John Rawls’ theory of justice as fairness, which emphasizes the importance of distributive justice and the equal enjoyment of fundamental rights for all citizens. Inequality in healthcare access remains a serious issue in Indonesia due to the uneven distribution of medical personnel, limited infrastructure, and disparities in service quality across regions. This research employs a normative juridical method with philosophical, conceptual, and statutory approaches, using primary legal sources such as the UUD NRI Tahun 1945, Undang-Undang Nomor 36 Tahun 2009 tentang Kesehatan, Undang-Undang Nomor 40 Tahun 2004 tentang Sistem Jaminan Sosial Nasional (SJSN), and Undang-Undang Nomor 6 Tahun 2023 tentang Cipta Kerja. The collection of legal materials was conducted through library research, and the data were analyzed qualitatively by interpreting legal norms and Rawls’ principles of justice in the context of equitable healthcare distribution. The findings show that the application of justice as fairness can be realized through policies promoting the equitable placement of medical personnel in underdeveloped regions, strengthening JKN, and implementing healthcare digitalization. This aligns with Pasal 28H ayat (1) and Pasal 34 ayat (3) UUD 1945, which affirm the State’s responsibility to guarantee every citizen’s right to adequate and equitable healthcare services.